Rapid dissemination of colistin and carbapenem resistant Acinetobacter baumannii in Central Greece: mechanisms of resistance, molecular identification and epidemiological data. Issue 1 (December 2015) - Oikonomou, O.; Sarrou, S.; Papagiannitsis, C.; Georgiadou, S.; Mantzarlis, K.; Zakynthinos, E.; Dalekos, G.; Petinaki, E.
Abstract Background Colistin-resistant/carbapenem-resistantAcinetobacter baumannii is a significant challenge for antibiotic treatment and infection control policies. Since 2012, in Central Greece an increase of colistin/pan- resistantA. baumannii has occurred, indicating the need for further analysis. Methods A total of 86 colistin-resistant/carbapenem-resistant out of 1228A. baumannii clinical isolates, consecutively collected between 2012 and 2014 in a tertiary Greek hospital of Central Greece, as well as one environmental isolate from surveillance cultures were studied. Molecular typing and mechanisms of resistance to colistin and to carbapenems were assessed, whereas, epidemiological and clinical data of the patients were reviewed. Results During the study period, the rate of colistin resistance gradually increased and reached 21.1 % in 2014. All colistin-resistant/carbapenem-resistantA. baumannii belonged to 3LST ST101 clone that corresponds to the international clonal lineage II. Carbapenem resistance was associated with the presence ofbla oxa-23-like, while resistance to colistin probably correlated with G54E and R109H amino acid substitutions in PmrA and PmrC, respectively. Conclusions Epidemiological data of the patients indicated that the first detection of colistin-resistant/carbapenem-resistant ST101 clone in the University Hospital of Larissa (UHL) was associated with a patient who previously had received colistin, while, the movement of the infected patients into the hospital probably resulted to its spread.